1996
DOI: 10.1007/bf00400672
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin enhances GLUT4 translocation through the increase of insulin receptor tyrosine kinase in primary adipocytes: evidence that bradykinin stimulates the insulin signalling pathway

Abstract: It has been suggested that bradykinin stimulates glucose uptake in experiments in vivo and in cultured cells. However, its mechanism has not yet been fully elucidated. In this study, the effects of bradykinin on the insulin signalling pathway were evaluated in isolated dog adipocytes. The bradykinin receptor binding study revealed that dog adipocytes possessed significant numbers of bradykinin receptors (Kd = 83 pmol/l, binding sites = 1.7 x 10(4) site/ cell). Reverse transcription-polymerase chain reaction am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…Because the kinin-kallikrein system is involved in sensitizing insulin action in peripheral tissues, 29,30 it is possible that the increased activity of tissue ACE leads to insulin resistance through the decrease of kallikrein levels. However, Dahl-S rats fed a normal diet demonstrated lower plasma and tissue angiotensin II than Dahl-R rats, but salt loading did not cause significant changes in angiotensin II levels in either strain.…”
Section: Discussionmentioning
confidence: 99%
“…Because the kinin-kallikrein system is involved in sensitizing insulin action in peripheral tissues, 29,30 it is possible that the increased activity of tissue ACE leads to insulin resistance through the decrease of kallikrein levels. However, Dahl-S rats fed a normal diet demonstrated lower plasma and tissue angiotensin II than Dahl-R rats, but salt loading did not cause significant changes in angiotensin II levels in either strain.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In the absence of BKB2R, mice showed normal insulin sensitivity but reduced glucose tolerance (Figures 1a-f). Additionally, 6-month-old obB2KO mice displayed a higher fasting hyperglycemia when compared with obWT (162.3±28.2 mg/dl vs 85.25±13.3 mg/dl, Figure 1g).…”
Section: Bkb2r Deficiency Potentiates Hyperglycemia and Reduces Glucomentioning
confidence: 99%
“…In isolated systems, it has been shown that BK can trigger the translocation of the glucose transporter 4 (GLUT4) in adipose tissue and muscle either directly 8 or by increasing insulin sensitivity. [10][11][12] Miyata et al 11 showed that BK can promote insulin action, augmenting both the phosphorylation of the insulin receptor …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bradykinin also increases glucose uptake in muscular cells and primary adipocytes by triggering GLUT4 (SLC2A4) translocation through insulin-dependent and -independent pathways (Isami et al 1996, Kishi et al 1998, Beard et al 2006. However, in humans, the effect of kinins on muscle glucose uptake remains controversial , Nuutila et al 1996, Mahajan et al 2004.…”
Section: Introductionmentioning
confidence: 99%